Economic and Business Studies Journals and Readership Information from Mendeley - Kaltrina Nuredini; Isabella Peters (Re:inventing Information Science in the Networked Society, Proceedings of the 14th International Symposium on Information Science, Zadar/Croatia, 19th—21st May 2015 (ISI 2015), 2015)
We present Mendeley-readership information for 30 journals from the German Handelsblatt ranking for Economics and Business Studies from 2010/2012. We use readership data to characterize both fields by journals with over twenty years of publication activity. The analysis focusses on journal output, reader counts, scientific disciplines, academic status as well as geographic origin of readers. The results show that Mendeley provides relatively good coverage of research articles for both disciplines. The majority of readers are PhD students in Business Administration from USA and Germany. Moderate correlations are found between journals' reader numbers and impact factors. The results suggest that Mendeley readership data on journal level adds useful information to research evaluation and journal rankings and helps economists to publish in the best journal according to the intended target groups.
Keywords: 330; altmetrics; readership information; journal ranking; economics